Effect of ferric oxide nanoparticles incorporation on structure and electrical properties of modified BNKT ceramics - Pharatree Jaita (2019)
© 2019 Trans Tech Publications, Switzerland. The BNKBST30 + 3 vol% Fe2O3 ceramic was fabricated via a solid-state mixed oxide and sintered 1125°C for 2 h. The effects of ferric oxide nanoparticles (Fe2O3) additive on phase evolution, microstructure and electrical properties, i.e. dielectric, ferroelectric and electric fieldinduced strain, of BNKBST30 ceramic was investigated. The obtain ceramic was well sintered and densely with high density of 5.78 g/cm3. X-ray diffraction pattern and Raman spectra analysis showed a single perovskite with a mixed rhombohedral (R3c) and tetragonal (P4bm) phases. The obtained ceramic had a cubic-like grain shape with an average grain size of 0.82 μm. The dielectric constant as a function of temperature curves exhibited broad transition peaks at maximum temperature (Tm). The ceramic also showed good dielectric (ϵr = 1085, tan δ = 0.0496, ϵr,max = 6099, Tm = 296 °C), ferroelectric (Pr = 27.18 μC/cm2, Ec = 20.32 kV/cm, Rsq = 0.95), and electric fieldinduced strain properties (Smax = 0.22 %, Sneg = - 0.08 %, d∗33 = 440 pm/V). The obtained results indicated that the studied ceramic is considered as candidate for lead-free electromechanical applications.